Response of potato clones to planting dates in Pokhara, Kaski, Nepal - Adhikari, Saroj; Srivastava, Arvind Kumar; Sharma, Mohadutta; Shrestha, Arjun Kumar (Journal of Agriculture and Natural Resources, 2020)
A field trial was conducted to optimize the planting date and appropriate clone for ware potato production at Horticulture Research Station, Malepatan, Pokhara from October 2015 to March 2016. The trial was laid out in two factors Factorial Randomized Complete Block Design. There were nine treatments with three replications. The treatments comprised of three dates of planting (30th October, 14th and 29th November) and three potato clones (Janakdev, Lbr 40 and PRP 266264.1). The results showed that the main effects of planting dates and potato clones significantly (P<0.05) affected most growth, yield and yield attributing parameters of the crop. Interaction effect of planting dates and potato clones also significantly influenced the number of above-ground stems per plant, ground cover percentage, number of tubers per plant, number and weight of small size tuber (<25 g), weight of medium or seed size (25-50 g) tuber and large size (>50 g) tuber, number and yield of tubers per plot, and yield t/ha. The highest yield (37.05 t/ha) was obtained from 14th November planting. The clone Lbr 40 produced a higher yield (36.05t/ha). The clone PRP 266264.1 planting on 30th October planting produced significantly a higher yield (41.34t/ha). The clone Lbr 40 produced significantly highest number and weight of large size (>50 g) tuber. Number of small size (<25 g) tuber per plot or unmarketable tuber significantly increased on delayed planting.